Cold Energy Generation Characteristics of Adsorption Heat Pump Using Direct Heat Exchange Module - Ito, Mutsuhiro; Hasatani, Masanobu; Watanabe, Fujio (KAGAKU KOGAKU RONBUNSHU, 1996)
Heat and mass transfer characteristics in an adsorption heat pump (AHP) using a direct heat exchange module (DS-module) of silica gel were experimentally studied on the basis of results compared with those for the AHP with a multiple adsorbent-tube (MAT) type adsorber. Ultimate heat transfer enhancement for an adsorber of the AHP was almost achieved by using the DS-module and the possibility of its application to a refrigerator for producing low temperature cold heat energy was suggested.